Crime and the global political economy - Friman, Henry Richard (International political economy yearbook, 2009)
Crime and globalization / H. Richard Friman -- The internationalization of crime control / Peter Andreas and Ethan Nadelmann -- Crime, sovereignty and the offshore world / Ronen Palan -- Externalizing the costs of prohibition / H. Richard Friman -- Illicit commerce in peripheral states / William Reno -- Enabling norms and human trafficking / John T. Picarelli -- Governing finance in the war on terror / Marieke de Goede -- Immigrants and organized crime / Herman Schwartz -- Drug trafficking and the state in Mexico / Monica Serrano -- Social research, knowledge and criminal power / James H. Mittelman